SYNTHESIS, CHARACTERIZATION AND TESTING OF GRAPHITIC NANOFIBER FOR HYDROGEN ADSORPTION STUDY - SUFIAN, SURIATI (2010)
This research work focuses on the development of carbon nanomaterial particularly graphitic nanofibers by using chemical vapour deposition method. In addition, the development of catalyst for the synthesis of graphitic nanofibers has been investigated. For optimization of experimental parameters, Taguchi method has been used as the design of experiment. The capacity of the developed materials in hydrogen adsorption is tested at 77 K, 20 bar and 298 K, 100 bar using gravimetric measurement technique. For graphitic nanofiber (GNF) development, the preliminary experiments show that the most optimum temperature to produce the highest yield for both iron- and nickel-based GNF samples is 600°C. Other controlled parameters are not significant except for C2H4/H2 flow rate in nickel-based GNF samples synthesis where the maximum flow ratio (90/10) provides the highest yield in the reaction. In the GNF development, the modified experiment has improved the GNF yield from 6.4 to 12.1 g/(gcat.hr) in iron-based GNF samples and from 32.9 to 60.2 g/(gcat⋅hr) in nickelbased GNF samples. In additions, the optimum conditions to synthesize the highest yield of carbon nanotube (CNT) is when CNTs are produced in the reaction time of 40 minutes, H2 flow rate of 300 ml/min and the catalyst weight of 0.2 g using benzene as the carbon feedstock. The sample characterization using scanning electron microscope (SEM) and field emission scanning electron microscope (FESEM) has found that the average diameter size of CNTs varies from 90 to 210 nm and GNF varies from 100 to 200 nm. The use of transmission electron microscope (TEM) has proved that all CNTs are consist of multiwall nanotubes (MWNTs) while GNFs comprises of platelet and herringbone structures. Further characterization was done using Raman spectroscopy to obtain the purity of the sample by determining the relative value of amorphous carbon over graphite and the degree of graphitization. For the purpose of hydrogen adsorption study, the specific BET surface area of each sample is determined by surface area analyzer. The specific BET surface area of developed CNTs and GNFs are in the range of 51 to 121 m2/g and 60 to 293 m2/g, respectively. For hydrogen adsorption studies at 77 K and 20 bar conditions, the capacities using the developed GNFs are found to be between 0.58–0.64 wt% while at 150 bar, the weight percentage of the adsorbed hydrogen using GNFs is ranging from 0.06–0.30 wt% and at 100 bar, the capacities ranging from 0.07–0.27 wt%. The method used for adsorption studies focused on gravimetric measurement technique because of its high accuracy and less amount of sample is required as an adsorbent as compared with the conventional method that is the volumetric measurement. The experimental results also show that it is quite complex to realize the target of 6.5 wt% set by Department of Energy, USA either at 77 K or 298 K. Improvements in the development of CNTs and GNFs for hydrogen storage is a challenging task. Controlling the pore size distribution to be less than 1 nm and the micropore volume to be sufficient in enabling more hydrogen molecules to be stored are among the challenges. The presence of more open pores rather than close pores and tube encapsulation is very crucial.